Bright Young Women - Knoll, Jessica (Thorndike, Maine : Center Point Large Print, 2023)
"January 15, 1978, is a night of promise, excitement, and desire. A serial killers murderous spree in the Pacific Northwest couldnt be further from the minds of the vibrant young women at the top sorority on Florida State Universitys campus in Tallahassee. That night, Pamela Schumacher, president of the sorority, makes the unpopular decision to stay home. Startled awake at 3 a.m. by a strange sound, she makes the fateful decision to investigate. What she finds outside her bedroom door is a scene of implausible violence -- two of her sisters dead; two others, maimed. On the other side of the country, in Seattle, Tina Cannon has found peace after years of hardship. A chance encounter brings twenty-five-year-old Ruth Wachowsky into her life and they forge an instant connection. But then Ruth goes missing from Lake Sammamish State Park in broad daylight, the same day as another young woman, surrounded by thousands of beachgoers. Both vanish without a trace. Tina is convinced Ruth was a target of the man the papers refer to as the All-American Sex Killer. When she learns of the massacre in Tallahassee, Tina is convinced its him again. She rushes to Florida, on a collision course with Pamela -- and one last impending tragedy."--
Keywords: Bundy, Ted -- Fiction; Serial murders -- Fiction; Victims of violent crimes -- Fiction; Women -- Crimes against; Fiction; College sorority members -- Crimes against; Fiction; Florida -- Fiction; Washington (State) -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Historical fiction; Large print books